DIMENSI ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS ILMU DALAM MERESPONS KRISIS NILAI PADA DUNIA PENDIDIKAN MODERN - Hayati, Hazimah Dzikra; Restu, Riza; Nellitawati, Nellitawati; Jasrial, Jasrial; Sulastri, Sulastri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Modern education is currently facing a severe value crisis that affects all components of the educational system. This article aims to critically examine how the ontological, epistemological, and axiological dimensions of knowledge can serve as a philosophical foundation in responding to this crisis. Using a library research approach, this study analyzes academic and philosophical literature from both general and Islamic education perspectives. The findings reveal that the reduction of knowledge to a mere technical tool has resulted in the neglect of education's humanistic dimension. The ontological dimension emphasizes education as a space for meaning-making and existential development. The epistemological dimension highlights the importance of reflective and transdisciplinary thinking in constructing knowledge. Meanwhile, the axiological dimension affirms that education must uphold moral, ethical, and spiritual values. This study concludes that reorienting education based on the philosophy of science is crucial to building an education system that excels not only academically but also in moral and civilizational values.